Efektivitas Penerapan Jobsheet pada Pembelajaran Praktek Instalasi Motor Listrik - Fitri Winda Ilma Yanti; Aswardi Aswardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
Practical learning on Electric Motor Installation is one of the lessons in class XI and XII TITL at SMKN 5 Solok Selatan. Learning activities have not been effective because students only use a sheet of worksheets, where the worksheets used only contain pictures of a series of work made by students themselves before practicing. The purpose of the study was to obtain valid, practical and effective results of the Electric Motor Installation practice worksheet. Using the 4D development research method with 4 stages of activity, namely define, design, develop, and dessiminate, validity tests, practicality tests, and effectiveness tests have been carried out on the jobsheet. The results of the practicality test of the Electric Motor Installation practice worksheet are stated in the very valid category, the results of the practicality test of the worksheet are stated in the very practical category. The results of the josbheet effectiveness test stated that the jobsheet was effectively used. The conclusion of the research is that the Jobsheet is declared valid, practical, and effectively used in the practice of installing an electric motor for class XI TITL at SMKN 5 Solok Selatan.